Angiographic anatomy of the coronary sinus venous system in adult Kashmiri population - Samoon, Sayma; Mohiuddin, Khalid; Itoo, Mohammad Saleem; Dar, Khurshid Ahmad; Zargar, Parvez Ahmad; Andrabi, Syed Manzoor Ali (International Journal of Research in Medical Sciences, 2019)
Background: Knowledge of the coronary sinus venous anatomy is an important factor because of its relevance in electrophysiological procedures such as chronic resynchronisation therapy, mapping and ablation of arrhythmias. The advent of advanced invasive and interventional cardiac treatment and management tools for common disorders like heart failure has made understanding of coronary sinus anatomy necessary. The aim was to study the angiographic anatomy of coronary sinus and its tributaries in adult Kashmiri population and provide anatomical basis for cannulation of coronary sinus and its tributaries. Methods: Authors analysed the levophase angiogram of 150 subjects undergoing routine coronary angiography in the right anterior oblique and left anterior oblique view with the necessary caudal or cranial angulations. Results: The coronary sinus was formed by the union of GCV+LMV in 93.3% of subjects and by the union of GCV+PLV in 6.7% of subjects. The GCV and the MCV were the most consistent tributaries present in all the subjects. The mean length of CS was 71.70±9.7 mm when it was formed by GCV+LMV and 70.18±14.98 mm in case of GCV+PLV. The diameter of the CS ostium was 8.48±1.21mm. The mean diameter of GCV was 2.90±1.24 mm, MCV was 2.76±1.08 mm, LMV was 2.23±0.51 mm and the PLV was 2.25±0.53 mm. The opening angle of GCV was obtuse in all the cases, MCV drained at an acute angle in 62% subjects and LMV draining angle was acute in 31.33% cases. The valve of the CS was present in 32.7% subjects and absent in 67.3% subjects. The tortuosity was absent in 75.3%. The distance between CS ostium and the ostium of the vein ideal for lead implantation was between 10-40 mm in 76% subjects. Conclusions: The basic knowledge of coronary sinus and its tributaries play a significant role during electrophysiological procedures. The data obtained from the study can be utilised by interventional cardiologist for cannulation of coronary sinus in Kashmiri population.